До видового складу кліщів-фітосейід (Parasitiformes: Phytoseiidae) заповідника "Єланецький степ" - Bondarev, V. Yu. (public organization "Ukrainian Entomological Society", I.I. Schmalhausen Institute of Zoology of National Academy of Sciences of Ukraine, Institute of Plant Protection of National Academy of Agrarian Sciences of Ukraine, 2018)
As material for this work the gatherings of the author executed in 2016 year. On 43 species of plants 85 samples in which 249 copies of phytoseiid mites are revealed are taken. For the statistical analysis used an occurrence index (P1, %) and an index of domination of Paliya-Kovnatski (Di). Species structure of predatory phytoseiid mites (Parasitiformes: Phytoseiidae) in plant associations of state reserve "Elanetskyi step" (Mykolaiv region, Ukraine) were studied at the first time. 21 species of 7 genera of the family are detected (A. andersoni, A. herbarius, A. maior, N. marginatus, N. reductus, N. tauricus, E. finlandicus, D. echinus, T. tiliarum, P. intermixtus, P. soleiger, A. caudiglans, A. rapida, A. pirianykae, A. recki, A. verrucosa, A. spectata, T. cotoneastri, T. laurae, T. tiliae). Frequency of occurrence and fidelity to different types of plant communities for each species of mites were determined. Amlydromella (s. str.) recki, the most common species, was with occurrence index 35.3%. The species Amblydromella (s. str.) rapida, Amblydromella (Litoseia) spectata, and Paraseiulus intermixtus were the rare species (one specimen of each species was presented at collections). Amblydromella (s. str.) recki was the dominant in the complex of plant-feeding predatory mites. Three species, A. pirianykae, A. andersoni and E. finlandicus, were the subdominants. Typhlodromus cotoneastri was the subdominant of the first order. The remaining 16 species were the secondary members of the complex.